The ecology of the reptiles and amphibians in the Burkea africana - Eragrostis pallens savanna of the Nylsvley Nature Reserve - Brain, Charles Kimberlin (Bob) (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2008.